Economic Consequences of the AOCI Filter Removal for Advanced Approaches Banks - Kim, Sehwa; Kim, Seil; Ryan, Stephen G. (The Accounting Review, 2019)
ABSTRACT We examine economic consequences of U.S. bank regulators' phased removal of the prudential filter for accumulated other comprehensive income for advanced approaches banks beginning on January 1, 2014. The primary effect of the AOCI filter is to exclude unrealized gains and losses on available-for-sale securities from banks' regulatory capital. We predict and find that, to mitigate regulatory capital volatility resulting from the filter removal, advanced approaches banks increased the proportion of investment securities classified as held-to-maturity, thereby limiting their financing and interest rate risk management options, and they decreased securities risk, thereby reducing their interest rate spread. We further predict and find that these banks borrow more under securities repurchase agreements potentially collateralized by held-to-maturity securities and reduce loan supply owing to their reduced financing options, and that they increase loan risk to mitigate the decrease in their interest rate spread. JEL Classifications: G21; G28; M41; M48. Data Availability: Data are available from the public sources cited in the text.